Amicus curiae in enriching the consideration of judges when making decision on criminal case - Amanda Octavieni Bakhtiar; M. Raja Saputra. K; Dheny Wahyudhi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This study aims to determine and analyze how amicus curiae can enrich the consideration of judges' decisions to impose a criminal case decision and to determine and analyze the contribution of amicus curiae in criminal cases in Indonesian courts by Supreme Court Judges. Methods: The research method uses the Normative Juridical type, with in-depth analysis of several decisions, literature, journals, and doctrines. Findings: The results show that amicus curiae is not explained normatively in Indonesian legislation because it is a legal system adopted from the United States. Judges in handing down a decision can never be separated from the social desires demanded by reality, this makes judges have to carefully consider the decision of a case until an additional opinion from an amicus curiae is needed. It was found that amicus curiae as a